Comparisons within the Rice GA 2-Oxidase Gene Family Revealed Three Dominant Paralogs and a Functional Attenuated Gene that Led to the Identification of Four Amino Acid Variants Associated with GA Deactivation Capability - Hsieh, Kun-Ting (Rice (N Y), 2021)
BACKGROUND: GA 2-oxidases (GA2oxs) are involved in regulating GA homeostasis in plants by inactivating bioactive GAs through 2β-hydroxylation. Rice GA2oxs are encoded by a family of 10 genes; some of them have been characterized, but no comprehensive comparisons for all these genes have been conducted. RESULTS: Rice plants with nine functional GA2oxs were demonstrated in the present study, and these genes not only were differentially expressed but also revealed various capabilities for GA deactivation based on their height-reducing effects in transgenic plants. Compared to that of wild-type plants, the relative plant height (RPH) of transgenic plants was scored to estimate their reducing effects, and 8.3% to 59.5% RPH was observed. Phylogenetic analysis of class I GA2ox genes revealed two functionally distinct clades in the Poaceae. The OsGA2ox3, 4, and 8 genes belonging to clade A showed the most severe effect (8.3% to 8.7% RPH) on plant height reduction, whereas the OsGA2ox7 gene belonging to clade B showed the least severe effect (59.5% RPH). The clade A OsGA2ox3 gene contained two conserved C186/C194 amino acids that were crucial for enzymatic activity. In the present study, these amino acids were replaced with OsGA2ox7-conserved arginine (C186R) and proline (C194P), respectively, or simultaneously (C186R/C194P) to demonstrate their importance in planta. Another two amino acids, Q220 and Y274, conserved in OsGA2ox3 were substituted with glutamic acid (E) and phenylalanine (F), respectively, or simultaneously to show their significance in planta. In addition, through sequence divergence, RNA expression profile and GA deactivation capability analyses, we proposed that OsGA2ox1, OsGA2ox3 and OsGA2ox6 function as the predominant paralogs in each of their respective classes. CONCLUSIONS: This study demonstrates rice has nine functional GA2oxs and the class I GA2ox genes are divided into two functionally distinct clades. Among them, the OsGA2ox7 of clade B is a functional attenuated gene and the OsGA2ox1, OsGA2ox3 and OsGA2ox6 are the three predominant paralogs in the family. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12284-021-00499-4.